Vázlat a területi tervezés és a közigazgatás kapcsolatáról, avagy a regionalizálás a területi tervezés szemszögéből - Pfeil, Edit (Tér és Társadalom, 1999)
Hungarian public administration is facing the challenge of modernisation. One of the basic questions is the role of regions in the system of state in the process of EU enlargement. At the same time with the EU-conform establishment of the Hungarian institution of regional development, regions became regional development and statistical units. In the near future the answer has to be given to the following questions. Do the Hungarian regions have to integrate into the public administration? Do they have to become a governmental level with directly selected body? The study likes to approach this problem from the view of spatial planning, notdely from the aspect of institutions of regional planning. The presentation of institutional background of spatial planning in other countries in the first part of the study expresses the focus on the relationship between regional planning and public administration. There is a different relationship between local government, or state dominant regional planning and local governmental sphere and organisations of public administration. There is an individual and particular institutional system of regional planning in Hungary from this point of view, because two separated structures has been established for development and planning. Strategic planning is settled to regional development councils in the leve! of regions and counties, but regional planning belongs to local governments. In Hungary the local governments have built up in the levels of settlements and counties, while sooner or later regional level has to become dominant in connection with regional development. There are countries where administrative/local governmental level has the functions of planning regions. The analysis of foreign experiences prove that this countries both the administration and the planning decision making function are supplied by the same political body usually the direct elected body. There are no parallel duplicated organisations and structures only for regional planning. It is not merely saving, but also because the regional public bodies are capable to articulate the regional interests. There are independent planning regions from administrative regional division in federalised countries. In that case, the determination of planning regions is primarily based on the gravitation area of higher centres. In Hungary planning regions are artificial formations. Borders of spatial planning and public administration are matched in the current middle level of local government (county), though they operate in two different bodies. In the process of public administration reform the regionalisation of public administration and the keeping of regional planning-statistical units may seemed a rationalised solution instead of the duplication of structures. Besides the strengthening of the county government in the current county level the regional development unit elimination could be proposed.